Scientific Journalism as an Educational Practice: An Experience Report of the Collective Construction of a "Science Clothesline". Issue 2 (April 2020) - Galvão, Tássia; Felicio, Cinthia Maria; Ferreira, Júlio César; Noll, Matias
The aim of this study is to analyze how students understand scientific dissemination. Educational practice has shown that texts from traditional communication vehicles are attractive to students, and furthermore, students understood topics covered in the resources, assessing the language as simple and easy to understand. The applied methodology and the means of carrying out the activities contributed to a more dynamic learning environment in which possibilities permeated the connections between the proposed content and the students' daily lives, thus facilitating the understanding of scientific subjects by the students. One of the biggest difficulties was the writing component of the activities.